Dynamic Changes of Metabolite Profiles in Maternal Biofluids During Gestation Period in Huanjiang Mini-Pigs - Qian Zhu (Frontiers in Veterinary Science, 2021)
The biochemical parameters related to nitrogenous metabolism in maternal biofluids may be linked and even reflect the fetal metabolism and growth. The present study have measured the concentrations of various parameters related to amino acid (AA) and lipid metabolism, as well as different metabolites including the free AAs in maternal plasma and amniotic and allantoic fluid corresponding to fetuses with different body weight (BW) during different gestation periods, in order to identify the possible relationships between biochemical parameters and fetal growth. A total of 24 primiparous Huanjiang mini-pigs were fed with a standard diet. Data showed that, from day 45 to day 110 of gestation, the maternal plasma levels of alanine aminotransferase (ALT), albumin (ALB), Ile, Orn, Car, α-ABA, and β-AiBA increased (P < 0.05); while the levels of ammonia (AMM), choline esterase (CHE), high density lipoprotein-cholesterol (HDL-C), Leu, Glu, Cys, Asp, and Hypro decreased (P < 0.05). From day 45 to 110 of gestation, the amniotic fluid levels of aspartate transaminase (AST), CHE, total protein (TP), and urea nitrogen (UN) increased (P < 0.05), as well as the level of CHE and TP and concentration of Pro in allantoic fluid; while the amniotic fluid concentrations of Arg, Glu, Orn, Pro, and Tau decreased (P < 0.05), as well as allantoic fluid concentrations of Arg and Glu. At day 45 of gestation, the amniotic fluid concentrations of Arg, Orn, and Tau corresponding to the highest BW (HBW) fetuses were higher (P < 0.05), whereas the allantoic fluid concentrations of His and Pro were lower (P < 0.05) when compared with the lowest BW (LBW) fetuses. At day 110 of gestation, the amniotic fluid concentration of Tau corresponding to the HBW fetuses was higher (P < 0.05) than the LBW fetuses. These findings show that the sows display increased protein utilization and decreased lipid metabolism and deposition from day 75 to 110 of gestation. In addition, our data are indicative of a likely stronger ability of HBW fetuses to metabolize protein; and finally of a possible key role of Arg, Gln, Glu, Pro, Tau, and His for the fetal growth and development.